Opłata skarbowa jako źródło dochodów gmin: Stamp duty as a source of commune incomes - Świrska, Anna (Management and Administration Journal, 2021)
Public fees, as a source of incomes for Polish communes, constitute an extremely wide set. Their structure and the way of collection have an impact on autonomous decision making by the commune authority. Stamp duty is considered one of the oldest public fees and has the nature of a general administrative fee for official activities, such as: issuing permits for conducting business activities and the extension of visas. The revenue from this fee is the highest among all local fees and charges. The purpose of this article is to present regulations concerning stamp duty, as well as to define its place in the catalogue of a communes budget revenue.